2022
DOI: 10.1002/anie.202207512
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed MoOx on Rhodium Metallene Boosts Electrocatalyzed Alkaline Hydrogen Evolution

Abstract: Accelerating slow water dissociation kinetics is key to boosting the hydrogen evolution reaction (HER) in alkaline media. We report the synthesis of atomically dispersed MoO x species anchored on Rh metallene using a one-pot solvothermal method. The resulting structures expose the oxide-metal interfaces to the maximum extent. This leads to a MoO x -Rh catalyst with ultrahigh alkaline HER activity. We obtained a mass activity of 2.32 A mg Rh À 1 at an overpotential of 50 mV, which is 11.8 times higher than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 41 publications
0
60
0
Order By: Relevance
“…Recently, self-assembled porous architectures from individual building blocks have triggered tremendous attention. Particularly, noble metal aerogels (NMAs) involving macroscopic assembly systems represent the most important class of functional nanomaterials with the collective characteristics of noble metal (e.g., high electrical conductivity, excellent catalytic activities, and special plasmonic behavior) and aerogels (e.g., self-supported feature, continuous porous structure, and superior specific surface area), making them of great interest for a wide range of applications such as electrocatalysis and sensing. Thus, rationally tuning the morphology and electronic properties of building blocks of NMAs offers a promising method to design highly efficient NMAs. Two-dimensional (2D) materials have received great interest thanks to the large lateral size, high electronic conductivity, and highly exposed surface active sites. , Among them, an emerging class of ultrathin 2D nanomaterials, known as metallene, possess atomic-level dimensions and curved microstructures, which increase the accessible active sites and broad applications in sustainable energy conversion. In addition, single-atom doping is also an attractive approach to improve the electrocatalytic activity of the catalysts due to high atomic utilization and a tunable electronic structure. Hence, it is appealing to combine metallene with single-atom doping to create single-atom doping metallene building blocks. Assembling them into three-dimensional (3D) nanostructures enables the synthesis of advanced NMAs, which are expected to retain the functions of single-atom doping metallene and inherit the properties of aerogels, thus greatly promoting electrocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, self-assembled porous architectures from individual building blocks have triggered tremendous attention. Particularly, noble metal aerogels (NMAs) involving macroscopic assembly systems represent the most important class of functional nanomaterials with the collective characteristics of noble metal (e.g., high electrical conductivity, excellent catalytic activities, and special plasmonic behavior) and aerogels (e.g., self-supported feature, continuous porous structure, and superior specific surface area), making them of great interest for a wide range of applications such as electrocatalysis and sensing. Thus, rationally tuning the morphology and electronic properties of building blocks of NMAs offers a promising method to design highly efficient NMAs. Two-dimensional (2D) materials have received great interest thanks to the large lateral size, high electronic conductivity, and highly exposed surface active sites. , Among them, an emerging class of ultrathin 2D nanomaterials, known as metallene, possess atomic-level dimensions and curved microstructures, which increase the accessible active sites and broad applications in sustainable energy conversion. In addition, single-atom doping is also an attractive approach to improve the electrocatalytic activity of the catalysts due to high atomic utilization and a tunable electronic structure. Hence, it is appealing to combine metallene with single-atom doping to create single-atom doping metallene building blocks. Assembling them into three-dimensional (3D) nanostructures enables the synthesis of advanced NMAs, which are expected to retain the functions of single-atom doping metallene and inherit the properties of aerogels, thus greatly promoting electrocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Rhodium (Rh) is the nearest metal to Platinum (Pt) located at the vertex of volcano plot with small Gibbs free energy 13 , and has been demonstrated have excellent catalytic stability. Distinct from bulk metals, the intrinsic activity of the catalyst has been demonstrated to strongly depend on the size, the exposed defects, and the supports [14][15][16][17][18][19] . As an important traditional metal support, carbon materials show great application value in catalysis field, therefore, carbon materials are considered as the key component of highperformance catalysts [20][21][22] .…”
mentioning
confidence: 99%
“…During the subsequent water dissociation process, H* is more easily adsorbed on the W atoms of the W side in N–W 2 C/W due to the larger Δ G H* of W, while OH* is more likely to be adsorbed on the W atoms of the N–W 2 C side. As clearly depicted in Figure d, the N–W 2 C/W exhibits stronger adsorption on both the initial state H 2 O* and the final state H* + OH*, which can facilitate the Volmer reaction and accounts for the enhanced HER activity in alkaline and neutral electrolytes. , In addition, the standard tests of Pt(111) were performed (Figure S8). The results showed that Pt(111) exhibited better adsorption free energy for H* (−0.12 eV).…”
Section: Resultsmentioning
confidence: 99%
“…As clearly depicted in Figure 4d, the N−W 2 C/W exhibits stronger adsorption on both the initial state H 2 O* and the final state H* + OH*, which can facilitate the Volmer reaction and accounts for the enhanced HER activity in alkaline and neutral electrolytes. 58,59 In addition, the standard tests of Pt(111) were performed (Figure S8). The results showed that Pt(111) exhibited better adsorption free energy for H* (−0.12 eV).…”
Section: Resultsmentioning
confidence: 99%